Reforming the Approach to Alternative Dispute Resolution in Kenyan Industrial Disputes: A Comparative Analysis - Abenga, Elvis Begi Nyachieo (Department of Commercial Law, 2016)
Dispute resolution plays an important role in industrial relations. This is because conflicts are an inherent part in any relationship and industrial relationships are not exempt from this. To this end it is important to have a dispute resolution system that ensures efficient and effective resolution of disputes that arise in the course of industrial relationships. Efficient and effective dispute resolution is particularly important in the industrial relations arena as industrial relations attract various stakeholders, some who may not necessarily be a part of the dispute that arises, but who might inadvertently be affected in the situation of an unresolved dispute. Traditionally litigation has been the most commonly utilized medium of resolution of industrial disputes, with disputants rather choosing to take the dispute to the courts of law for adjudication and determination. However with the advent of alternative means of dispute resolution such as negotiation, mediation and arbitration, it has become paramount that these alternative dispute resolution methods be promoted for the reasons of expediency and efficiency. Regardless of the advent of such methods of dispute resolution, courts have still exercised some form of control and oversight of the dispute processes, and such oversight can be easily misused to defeat the main intention of having the alternative dispute resolution processes in the first place. This thesis discusses reforming the approach to alternative dispute resolution in Kenyan industrial disputes, so as to achieve maximum efficiency of the system. In doing this, the thesis does a comparative analysis of the systems of South Africa and Australia respectively.